BAYĀN AL-QUR’ĀN ‘AN HIDĀYAH AL-QUR’ĀN MIN KHILĀL TAFSĪR AL-ẒILĀL - Ismu Ridha Nurdin; Manshur Mahmud Abu Zinah (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
This study aims to collect, present, and analyze the Qur’ān’s talk about the guidance of Qur’ān, in Sayyid Quṭb’s al-Ẓilāl. To accomplish them, the researcher employed the inductive approach by collecting Qur’ānic verses that talk about the guidances of Qur’ān, and then locating the commentaries of the author of al-Ẓilāl on those verses. It was followed by the analytical approach by analyzing those collected verses, and finally the deductive approach by concluding issues that emerge from those examined verses relating to the Qur’ān’s talk about the guidance of Qur’ān. The researcher gathered several findings, among them: 1) The term of “al-Huda” in the Holy Qur’an has two meanings. The first, “Al-Hudā” in the sense of guidance, clarification, showing the path of truth, and clarifying the argument, and the second: “Al-Hudā” is the grace of God with success and infallibility for the servant. 2) Sayyid Qutb believes that the general or innate guidance is the greatest trust that God Almighty bestowed on all people, and that the Qur’anic guidance is the core of the miracle of the Qur’an. 3) The condition for attaining the guidance of the Qur’an is that a person has a sincere intention and corrects his aspiration when dealing with it. The second is looking and contemplating its noble verses, universal and legal. 4) The way of the Holy Qur’an in proving guidance is through exhortation and remembrance, which came in a variety of ways. 5) The goal of guidance in the views of the Qur’an is social change, and that is in two stages. The first stage is family readiness, and the second stage is social solidarity.